Being and becoming a female student and worker in gendered processes of vocational education and training. Issue 5 (4th July 2021) - Ledman, Kristina; Nylund, Mattias; Rönnlund, Maria; Rosvall, Per-Åke
ABSTRACT: This article reports results of an ethnographic study of how girls are positioned, and position themselves, in relation to gender regimes in three vocational programmes in Swedish upper secondary education: Restaurant Management & Food, Health & Social Care, and Vehicle & Transport. The comparison shows that there are different possible feminine positions where the girls resist and comply to varying degrees both within and between the programmes, with expectations interrelated with discourses of consumption, caring and production. However, generally the position of emphasised femininity is most prominent and becoming a female worker in the programmes' settings involves complying with feminine ideals of a caring discourse, regardless of whether the VET is oriented towards education for masculine production work, or feminine consumption work.